Control design of an unmanned hovercraft for agricultural applications - Garcia, Deyka I; White, Warren N (International Journal of Agricultural and Biological Engineering, 2015)
The efficient and precise application of agricultural materials such as fertilizer or herbicide can be greatly facilitated by autonomous operation. This is especially important under difficult conditions at remote sites. The purpose of this work is to develop an accurate nonlinear controller using a direct Lyapunov approach to ensure stability of an unmanned hovercraft prototype used for the execution of these agricultural tasks. Such a craft constitutes an underactuated system which has fewer actuators than degrees of freedom. The proposed closed loop system is simulated to demonstrate that a control law can stabilize both the actuated and unactuated degrees of freedom of the hovercraft. It is shown that the position and orientation of the hovercraft achieve high dynamic and steady performance.Keywords: controller, direct Lyapunov method, nonholonomic constraint, underactuated system, unmanned hovercraftDOI: 10.3965/j.ijabe.20150802.1468